Tinjauan Negara Hukum terhadap Perlakuan Diskriminatif Dalam Penempatan Dan Perlakuan Kerja: Kajian Putusan No. 41/Pdt.Sus-Phi/2023/Pn Bdg - Helen Yanti; Hendra Rahmani; Sri Nurcahyani (UIN Sunan Kalijaga Yogyakarta, 2025)
This study examines discriminatory treatment against workers within employment relations by analyzing Decision No. 41/Pdt.Sus-PHI/2023/PN Bdg as a case study. Employment relations in Indonesia’s legal framework are inherently subordinative, placing workers in a structurally weaker position compared to employers. Such imbalance creates space for both direct and indirect discriminatory practices, often disguised within internal company policies. A normative assessment of the 1945 Constitution, the Manpower Law, and its implementing regulations underscores the State’s obligation to provide legal protection through the principles of non-discrimination, legal certainty, and substantive justice. The analyzed decision demonstrates that the worker was subjected to job reassignment, consecutive warning letters, and termination of employment without adequate objective justification. These actions constitute indirect discrimination, as they appear formally legitimate yet substantively disadvantage the worker and reflect the employer’s misuse of authority. The panel of judges found that the employer’s actions lacked objective grounds and failed to uphold fairness within industrial relations. The court restored balance by granting the worker her entitlements, including compensation and process wages. This study emphasizes that legal protection for workers must not remain merely normative but must be effectively realized through judicial mechanisms. The analysis of the decision illustrates that labor law functions as a corrective instrument to rebalance power relations and prevent discriminatory practices detrimental to workers within employment settings.